Antibiotic Prophylaxis Trials in Obstetrics: A Call for Pediatric Collaboration - Rodney A. McLaren; Fouad Atallah; Howard Minkoff (Thieme Medical Publishers, Inc., 2020)
Surgical site infections are common complications of cesarean delivery. Many recent studies, including meta-analyses, have assessed the efficacy of antibiotic prophylaxis. Those articles have demonstrated that preincision antibiotic prophylaxis reduces the incidence of surgical site infections postcesarean, and that the use of adjunctive azithromycin further reduces infection after nonelective cesarean deliveries. However, long-term effects of fetal exposure to antibiotic prophylaxis-including asthma, obesity, and alterations in microbiota-have also been demonstrated. We suggest that while studies of optimal antibiotic regimens proceed, considerations of the potential risks to the neonate should be factored into discussions of benefits and burdens.